Nanotechnology in Cancer Diagnosis and Treatment - Noor Alrushaid; Firdos Alam Khan; Ebtesam Abdullah Al-Suhaimi; Abdelhamid Elaissari (MDPI AG, 2023)
Traditional cancer diagnosis has been aided by the application of nanoparticles (NPs), which have made the process easier and faster. NPs possess exceptional properties such as a larger surface area, higher volume proportion, and better targeting capabilities. Additionally, their low toxic effect on healthy cells enhances their bioavailability and t-half by allowing them to functionally penetrate the fenestration of epithelium and tissues. These particles have attracted attention in multidisciplinary areas, making them the most promising materials in many biomedical applications, especially in the treatment and diagnosis of various diseases. Today, many drugs are presented or coated with nanoparticles for the direct targeting of tumors or diseased organs without harming normal tissues/cells. Many types of nanoparticles, such as metallic, magnetic, polymeric, metal oxide, quantum dots, graphene, fullerene, liposomes, carbon nanotubes, and dendrimers, have potential applications in cancer treatment and diagnosis. In many studies, nanoparticles have been reported to show intrinsic anticancer activity due to their antioxidant action and cause an inhibitory effect on the growth of tumors. Moreover, nanoparticles can facilitate the controlled release of drugs and increase drug release efficiency with fewer side effects. Nanomaterials such as microbubbles are used as molecular imaging agents for ultrasound imaging. This review discusses the various types of nanoparticles that are commonly used in cancer diagnosis and treatment.